Gulma pada Lahan Kacang Tanah (Arachis hypogaea L.) di Kampung Meyeruk Papua Barat - Budirianto, Heru Joko; Lefaan, Paskalina Th.; Atanay, Yohanes (BIOMA: Jurnal Biologi dan Pembelajarannya, 2023)
Meyeruk village peanuts (Arachis hypogaea) were planted without a particular cropping pattern. This condition triggers Weed Diversity which can interfere with the growth of peanuts. This study aims to inventory the types of peanut weeds in two different land conditions in Meyeruk Village. The method used is descriptive method with direct observation technique. Weeds are carried out on flat and sloping land by making a combination of plotted paths. For each type of land, three observation plots were made, each plot measuring 2 m x 2 m with a distance of 3 m between the plots. The results obtained 14 Species of weeds, 5 species of weeds on flat land and 11 species of weeds on slopes. The type of weed that dominates and has the second largest number of individuals in the land type is Cynodon dactylon. The species with the highest importance index on flat land and slopes was Cynodon dactylon, with 120.83% and 59.53%, respectively.